2008
DOI: 10.1111/j.1524-475x.2008.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL RESEARCH–CLINICAL SCIENCE: Reducing wound pain in venous leg ulcers with Biatain Ibu: A randomized, controlled double‐blind clinical investigation on the performance and safety

Abstract: Six out of 10 patients with chronic wounds suffer from persistent wound pain. A multinational and multicenter randomized double-blind clinical investigation of 122 patients compared two moist wound healing dressings: a nonadhesive foam dressing with ibuprofen (62 patients randomized to Biatain Ibu Nonadhesive Coloplast A/S) and a nonadhesive foam without ibuprofen (60 patients to Biatain Non-Adhesive-comparator). Patients were recruited from September 2005 to April 2006. The ibuprofen foam was considered succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 28 publications
5
52
1
4
Order By: Relevance
“…Evidence based guidelines and experts in wound management recommend coordinated specialised leg ulcer services involving care providers at multiple levels, providing continuity and standardisation of care, to obtain optimal outcomes for adults with leg or foot ulcers which fail to show signs of healing within 4–12 weeks [24,43,44]. However, this study found less than half of the participants had been referred to a secondary level of care before admission to the study clinics with an average ulcer duration of 22 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence based guidelines and experts in wound management recommend coordinated specialised leg ulcer services involving care providers at multiple levels, providing continuity and standardisation of care, to obtain optimal outcomes for adults with leg or foot ulcers which fail to show signs of healing within 4–12 weeks [24,43,44]. However, this study found less than half of the participants had been referred to a secondary level of care before admission to the study clinics with an average ulcer duration of 22 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Dressing materials have experienced continuous and significant changes over the last years (29). They even might internalize different pharmaceutical compounds like antiseptics or analgetics to the wound surface (30). Debridement still ranks among the most important therapeutic approaches to reduce fibrin and bacterial burden and to induce wound healing by wound bed preparation.…”
Section: Debridement and Antimicrobial Effectsmentioning
confidence: 99%
“…To overcome side effects of systemically applied analgetics, a combination of moisture-balancing foam dressings with the release of low-dose nonsteroidal anti-inflammatory drugs (NSAID), that is, ibuprofen, was developed representing a new therapeutic class of local pain-relieving dressings. Gottrup et al [5] evaluated the outcome of patients treated with ibuprofen foam in a randomized controlled double-blind clinical investigation. Wound pain intensity in patients with venous ulcers was significantly reduced with the ibuprofen foam compared to the pain-reducing effect of moist wound therapy alone.…”
Section: Analgeticsmentioning
confidence: 99%